Leadership in Allied Health: A Review of the Literature - Patricia Bradd; Joanne Travaglia; Andrew Hayen (ACHSM, 2017)
Background: It is well established that effective clinical leadership improves the quality of healthcare service provision and promotes leadership outcomes. [1,2] Leadership capacity and capability of allied health professionals is needed for successful clinical service provision, [3] but less is known about allied health leadership than about other clinical groups. Aims: The literature review aimed to identify research about leadership and leadership development of allied health practitioners in healthcare settings. Methods: A database review was undertaken using SCOPUS, CINAHL, Medline and Business Elite databases from December 2014-September 2015. Three leadership journals were also hand searched. A total of 1665 articles were identified. These were scanned and 129 articles were retrieved with 70 articles shortlisted for indepth review. Results: After application of inclusion and exclusion criteria, seven journal articles were included in the literature review. Review of the studies identified two areas of primary focus: leadership styles and outcomes and leadership development programs. Conclusions: Findings showed that there are currently a limited number of robust published reports in relation to leadership and allied health practitioners. Implications for Practice: Well-designed research studies to further evaluate leadership skills of allied health practitioners as well as to determine the effectiveness of leadership programs in developing transformational leaders are required. Abbreviations: CASP - Clinical Appraisal Skills Program; NHMRC - National Health and Medical Research Council.